Inclusion of Students with Borderline Cognitive Impairment in Secondary Schools: Challenges and Coping Strategies - Egaga, Musa Moses; Effiom, Veronica Nakanda; Bullem, Anthony Godwin; Ejim, Egan Hilary; Nabiebu, Miebaka; Okenjom, Godian Patrick; Oko, Bernard Atrogor; Ekaette, Samuel Okpon; Ngwu, Maria Enemebe; Akpan, Augustine; Aloysius, Orogwu Alo; Egbai, Mercy Egbai; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: The challenges of managing students with borderline cognitive impairment in an inclusive classroom are enormous. Therefore, there is a need for appropriate coping strategies to foster the successful inclusion of students with borderline cognitive impairment in the day-to-day classroom activities. Aim: This study examines the challenges facing the inclusion of students with Borderline Cognitive Impairment (BCI) and the coping strategies often adopted by these students in the Ogoja Education Zone of Cross River State, Nigeria. Method: The study adopted a descriptive survey design. One hundred and sixty-nine students with BCI in twenty (2) regular secondary schools were selected, using the purposive sampling technique. The instrument for the study was a questionnaire titled "Academic Challenges and Coping Mechanism of Students with Borderline Cognitive Impairment Questionnaire (ACCMSBCIQ 0.67). Results: The study revealed that inclusive education for students with BCI at the secondary school level in the Ogoja Education Zone of Cross River State is hindered by a complex web of interconnected challenges. The study also revealed that students with BCI adopt several coping strategies to remain included in the secondary education program in the study area. Recommendation: Based on the findings of the study, the researchers recommend that the government and other stakeholders should organize adequate training on the inclusion of students with BCI for all secondary school teachers in Cross River State